Prevention of Fetal Alcohol Spectrum Disorder: Current Canadian Efforts and Analysis of Gaps - Nancy Poole; Rose A. Schmidt; Courtney Green; Natalie Hemsing (SAGE Publishing, 2016)
Effective prevention of risky alcohol use in pregnancy involves much more than providing information about the risk of potential birth defects and developmental disabilities in children. To categorize the breadth of possible initiatives, Canadian experts have identified a four-part framework for fetal alcohol spectrum disorder (FASD) prevention: Level 1, public awareness and broad health promotion; Level 2, conversations about alcohol with women of childbearing age and their partners; Level 3, specialized support for pregnant women; and Level 4, postpartum support for new mothers. In order to describe the level of services across Canada, 50 Canadian service providers, civil servants, and researchers working in the area of FASD prevention were involved in an online Delphi survey process to create a snapshot of current FASD prevention efforts, identify gaps, and provide ideas on how to close these gaps to improve FASD prevention. Promising Canadian practices and key areas for future action are described. Overall, Canadian FASD prevention programming reflects evidence-based practices; however, there are many opportunities to improve scope and availability of these initiatives.